Konsep Moderasi Beragama dalam Islam Perspektif Habib ‘Ali al-Jufri - Sutrisno, Andri; Arcylla, Dian Ratri (Advances In Social Humanities Research, 2024)
The rise of socio-religious conflicts that have occurred in Indonesia in recent years has caused the condition of Indonesian society to be threatened. Such as the case of acts of terrorism by ISIS networks and radical Islamic groups. Also the movement against pancasila by the leader of the Jemaah Islamiyah group, Abu Bakar Ba'asyir. One of the factors causing the emergence of religious social conflicts is the existence of differences in views and beliefs about something. Overcoming this, religious moderation is conceptualized as a powerful solution in controlling radical and extreme ideas. In this study, researchers felt the need to reexamine the concept of religious moderation from the frame of Islam in the view of Habib 'Ali al-Jufri. This research uses descriptive qualitative research methods with the type of literature research. The focus of research by researchers is taken from two points, namely; a) the concept of religious moderation in the Islamic perspective of Habib 'Ali al-Jufri; b) the relevance of the concept of religious moderation in Islam from Habib 'Ali al-Jufri's perspective to the religious diversity of Indonesian society. Religious moderation according to Habib 'Ali al-Jufri is a person's religious perspective or attitude while still maintaining human values. In such conditions, the similarity of form as a creature of Allah SWT becomes a factor to be generous with various differences. The concept of religious moderation by Habib 'Ali al-Jufri is very important and very relevant to be applied in Indonesia. Considering Indonesia with a Muslim majority and various mass organizations in it. Thus, the concept of humanizing humans is the main indicator in realizing the glory and glory of Muslims in Indonesia.